(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
In this article, narratives of bisexual women about their perceptions and experiences linked to dressing, bisexuality and their identity processes will be analyzed, as well as how the interlocutors’ corporal-aesthetic constructions relate to different environments, whether from the LGBTI+ community or heteronormative ones. As theoretical support, concepts from different areas of study were used, such as dressing (ENTWISTLE, 2015), from fashion studies, identity (CIAMPA, 1989) and life story narratives (ALVES, 2017), from social psychology, borders (ANZALDÚA), gender technology (LAURETIS, 1987), heterosexual matrix and performativity (BUTLER, 1990), from feminist and queer theories, and passability (EISNER, 2013) and the epistemic erasure contract of bisexuality (YOSHINO, 2000), from bisexual epistemologies. As a result of the narratives’ analysis, following the methodology of core meanings (AGUIAR;OZELLA, 2006), it was possible to understand that as there isn’t one (or some) specific aesthetic(s) which are socially related to bisexuality, the bisexual women’s experience is almost always one of passability—whether lesbian or heterosexual—and misrecognition, which can cause them to feel misunderstood and isolated. However, these same experiences of non-recognition and disengagement from prevailing corporal-aesthetic expectations can be seen as a fertile ground for questioning social norms and structures beyond the scope of dressing and sexuality